Stock Portfolio Performance Analysis in Estate Crop Subsector Using Sharpe Measure, Treynor Measure, and Jensen Measure - Artie Arditha Rachman; Igo Febrianto (Politeknik Negeri Lampung, 2012)
Investors form a stock portfolio in order to gain returns from several sources and distribute possible risks. Several methods are required when forming a stock portfolio to measure and evaluate portfolio performance. The current research showed different results of the Sharpe Measure, Treynor Measure, and Jensen Measure when measuring stock portfolio performance in estate crop companies listed in Indonesia Stock Exchange. The data used in this research were stock data of PT Astra Agro Lestari Tbk. (AALI), PT PP London Sumatera Tbk. (LSIP), and PT Bakrie Sumatera Plantation Tbk. (UNSP), data of stock composite index, and Bank of Indonesia rate, taken from January 2006 to January 2012. The Sharpe Measure result showed that best stock combination came from portfolio of AALI and LSIP, while The Treynor Measure and The Jensen Measure result showed that the best stock combination came from AALI and UNSP. The difference was caused by using of different risk variable in the calculation of each measurement. This difference makes investors have chances to decide which method is suitable to investor perception of risk in forming portfolio.Â Keywords: portfolio, Sharpe, Treynor, Jensen.